2004
DOI: 10.1002/cncr.20029
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Black/African American men for research on prostate cancer prevention

Abstract: Background: Endoscopic, endonasal, minimally invasive pituitary surgery (MIPS) has proven to be safe and efficacious. However, there are few data that assess the health‐related or sinonasal‐specific quality‐of‐life (QoL) of those undergoing MIPS. Our hypothesis is that patients undergoing MIPS do not have significantly different sinus disability or change in QoL after surgery compared to prior to surgery. Methods: This is a retrospective review of patients undergoing MIPS between 2002 and 2009. Rhinosinusitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 31 publications
1
66
0
Order By: Relevance
“…The men in the current study were willing to share the experiences they had with prostate cancer, although other studies have found that cancer is not talked about openly among African Americans because of its associated stigma (Gray, Fitch, Phillips, Labrecque, & Fergus, 2000;Woods, Montgomery, Belliard, Ramirez-Johnson, & Wilson, 2004;Woods, Montgomery, & Herring, 2004). The lack of suspicion and distrust of physicians and other healthcare providers was the most important finding in the present investigation.…”
Section: Discussionmentioning
confidence: 69%
“…The men in the current study were willing to share the experiences they had with prostate cancer, although other studies have found that cancer is not talked about openly among African Americans because of its associated stigma (Gray, Fitch, Phillips, Labrecque, & Fergus, 2000;Woods, Montgomery, Belliard, Ramirez-Johnson, & Wilson, 2004;Woods, Montgomery, & Herring, 2004). The lack of suspicion and distrust of physicians and other healthcare providers was the most important finding in the present investigation.…”
Section: Discussionmentioning
confidence: 69%
“…For AfricanAmericans, this may be associated with the distrust of the health care system after the experience of racism and exploitation in medical research. 44,45 A few exceptions are worth noting. Jenkins et al 46 surveyed 1112 white and 118 African-American men about their sexual functioning before and after prostate cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…15 It is unclear whether the topic of weight management is uninteresting to men, but challenges in recruitment of African American men into biomedical research have been well documented. [27][28][29][30] The study sample is very educated when compared to randomly-selected national samples of African American women. In NHANES 1999-2006, 49 % of participants had at least some college education 31 compared to 91 % in this sample, thus potentially limiting its applicability to the larger African American population.…”
Section: Discussionmentioning
confidence: 99%